Bibliometric analysis of published literature on women's rights from Islamic perspective - Elshobake, Mohammed R. M. (RSIS International: Research and Scientific Innovation Society, 2024)
Research on women's rights from an Islamic perspective in the Scopus database was initiated in 1979, which discussed the role of women of the Muslim Hausa tribe in Nigeria. Since then, the research in that field has been increasingly used by researchers to examine further issues related to women's rights from an Islamic perspective. The study aims to explore the published literature related to the topic of “women's rights from an Islamic perspective”. The Scopus database was used to collect all relevant articles. Publish or perish was used to incorporate the obtained data, VOSviewer to visualize the data, and Microsoft Excel to examine the collected data. Standard bibliometric analysis was used to offer full information on the increase of publications, research output, and citation analysis. According to research findings, a total of 484 documents were retrieved. It was discovered that there was no gap in publications since 2000 and the annual growth rate of published material on women’s rights from an Islamic perspective has grown since 2006. Most of the articles were published in journals, mainly in English, with most of the research on women’s rights from an Islamic perspective being in the Social Sciences field. “Women’s Rights”, “Islam” and “Human Rights” were the most popular keywords and represent the primary study areas comprised in the topic of women’s rights from an Islamic perspective. Many the research related to the study field was conducted in the United States and the United Kingdom. This study shows the development of published literature on women’s rights from an Islamic perspective, the subjects related to women’s rights from an Islamic perspective in which researchers are currently interested, as well as possible directions for future research on the study field.